COMPARATIVE ANALYSIS OF COMPLICATIONS AFTER HOLMIUM LASER ENUCLEATION OF THE PROSTATE (HOLEP) AND TRANSURETHRAL RESECTION OF THE PROSTATE (TURP) IN PATIENTS WITH BENIGN PROSTATIC HYPERPLASIA - Kasimov S.S (Western European Studies, 2026)
to conduct a comparative analysis of the incidence and nature of postoperative complications in patients with benign prostatic hyperplasia (BPH) after holmium laser enucleation of the prostate (HoLEP) and transurethral resection of the prostate (TURP).
Keywords: Benign prostatic hyperplasia; HoLEP; TURP; postoperative complications